PROBLEMS OF THE CREATION OF TERRITORIAL COMPLEXES ON THE WORLD DIAMOND MARKET - Pototskaya, Tatyana Ivanovna (Quaestiones Geographicae, 2016)
The main focus of the paper is on one of the most significant issues of economic geography nowadays, namely ways of an efficient distribution of facilities on the basis of inter-industry complexity (on the example of the diamond industry). The description of the formation of the complex branch of the diamond industry is carried out in several stages: determining the cause of inter-sectoral cooperation in the diamond industry; investigating territorial features of the complex that belongs to ABA, the most important of which is the difficulty of forming the WPK national (country) level; defining a cluster as the main form of territorial complexity characteristic of ABK (its types and causes of formation, characteristics of each cluster); and drawing conclusions about the appropriate degree of territorial concentration of various activities under the ABA type of market for which they are characterised. Special attention is paid to the identification and examination of territorial complexity types in the diamond complex in Russia.